Mammary gland of the rock cavy (Kerodon rupestris -Wied Neuwied, 1820): morphologic aspects - Lima, Marcelo Cardoso de; Bonatelli, Marina; Oliveira, Moacir Franco de; Miglino, Maria Angélica; Goiozo, Paulo Felipe Izique; Martins, Simone Maria Massami Kitamura; Carvalho, Ana Flávia de (Brazilian Journal of Veterinary Research and Animal Science, 2008)
In attempt to collaborate with the rational zootecnic exploration of the Rock Cavy (Kerodon rupestris), the morphology of the mammary gland from these rodends was described, so that it can become a food source for northeastern population. Were used five animals yielded by the Center of Multiplication of Animals Savage (CEMAS), created by the Superior School of Agriculture of Mossoró (ESAM) registered in IBAMA as scientific breeding with number 12,492- 0004. The mammary glands were remove through dissecation and were photographed. Each animal presented two mammary glands in the base of the insertion of the pelvic members in the abdominal region. Histologicaly the mammary gland is composed of a great amount of lobes, replete of alveolar tubs glands with cubical simple epithelium. Its mammary papilla showed an amount of muscular staple fibres in circular way that assists it in the contraction for excrement of milk.